Au⋅⋅⋅H−C Hydrogen Bonds as Design Principle in Gold(I) Catalysis. (18th August 2021) - Darmandeh, Heidar; Löffler, Julian; Tzouras, Nikolaos V.; Dereli, Busra; Scherpf, Thorsten; Feichtner, Kai‐Stephan; Vanden Broeck, Sofie; Van Hecke, Kristof; Saab, Marina; Cazin, Catherine S. J.; Cavallo, Luigi; Nolan, Steven P.; et al.
Abstract: Secondary ligand–metal interactions are decisive in many catalytic transformations. While arene–gold interactions have repeatedly been reported as critical structural feature in many high‐performance gold catalysts, we herein report that these interactions can also be replaced by Au⋅⋅⋅H−C hydrogen bonds without suffering any reduction in catalytic performance. Systematic experimental and computational studies on a series of ylide‐substituted phosphines featuring either a PPh3 ( Ph YPhos) or PCy3 ( Cy YPhos) moiety showed that the arene‐gold interaction in the aryl‐substituted compounds is efficiently compensated by the formation of Au⋅⋅⋅H−C hydrogen bonds. The strongest interaction is found with the C−H moiety next to the onium center, which due to the polarization results in remarkably strong interactions with the shortest Au⋅⋅⋅H−C hydrogen bonds reported to date. Calorimetric studies on the formation of the gold complexes further confirmed that the Ph YPhos and Cy YPhos ligands form similarly stable complexes. Consequently, both ligands showed the same catalytic performance in the hydroamination, hydrophenoxylation and hydrocarboxylation of alkynes, thus demonstrating that Au⋅⋅⋅H−C hydrogen bonds are equally suited for the generation of highly effective gold catalysts than gold‐arene interactions. The generality of this observation was confirmed by a comparative study between a biaryl phosphine ligand and its cyclohexyl‐substituted derivative, which again showed identical catalytic performance. These observations clearly support Au⋅⋅⋅H−C hydrogen bonds as fundamental secondary interactions in gold catalysts, thus further increasing the number of design elements that can be used for future catalyst construction. Abstract : Experimental and computational studies on PPh3 and PCy3 ‐substituted ylide‐functionalized phosphines as well as on a biaryl and a cyclohexyl‐aryl phosphine demonstrate that Au⋅⋅⋅H−C hydrogen bonds can serve as secondary metal ligand interactions similar to gold–arene interactions often used in ligand design for the stabilization of catalytically active species. Remarkably short Au−H bonds are observed.